Analisis Lagu Toraja Marendeng Marampa Aransemen Tindoki Band - Linesti Lamba; Ni Wayan Ardini; I Komang Darmayuda; Ketut Sumerjana (Institut Seni Indonesia Denpasar, 2019)
This study aims to describe the musical form of Marendeng Marampa'